Identification of a common recognition center for a photoactive non-steroidal antiinflammatory drug in serum albumins of different species. Issue 1 (29th November 2018) - Molins-Molina, Oscar; Lence, Emilio; Limones-Herrero, Daniel; González-Bello, Concepción; Miranda, Miguel A.; Jiménez, M. Consuelo
Abstract : Photoreactivity, proteomic and molecular dynamic simulation studies demonstrate the existence of a common recognition center for carprofen in serum albumins of different species, in the interface between subdomains IB and IIIA. Abstract : The non-steroidal anti-inflammatory drug ( S )-carprofen (CPF ) has been used as a photoactive probe to investigate the possible existence of a common recognition center in serum albumins (SAs) of different species. The methodology involves irradiation of theCPF /SA complexes, coupled with gel filtration chromatography or proteomic analysis of the photolysates, docking and molecular dynamics simulations. Photolysis ofCPF /SA complexes at λ = 320 nm, and gel filtration chromatography, revealed that the protein fraction still contained the drug fluorophore, in agreement with covalent attachment of the photogenerated radical intermediateCBZ˙ to SAs. After trypsin digestion and ESI-MS/MS, the incorporation ofCBZ˙ was detected at several positions in the different albumins. Remarkably, modifications at the IB/IIIA interface were observed in all cases (Tyr452 in HSA, RbSA and RtSA and Tyr451 in BSA, PSA and SSA). The molecular basis of this common recognition, studied by docking and molecular dynamics simulation studies on the corresponding non-covalent complexes, corroborated the experimentally observed covalent modifications. Our computational studies also revealed that the previously reported displacement ofCPF by ( S )-ibuprofen, a site II specific drug, would be due to an allosteric effect in site II, rather than a direct molecular displacement, as expected.